Validity of an ankle joint motion and position sense measurement system and its application in healthy subjects and patients with ankle sprain. Issue 131 (July 2016) - Lin, Chueh-Ho; Chiang, Shang-Lin; Lu, Liang-Hsuan; Wei, Shun-Hwa; Sung, Wen-Hsu
Highlights: A novel measurement system can be used to measure ankle ROM and perception in multiple planes under weight-bearing condition. The programmable graphic user interface and data management for this developed system with excellent validity was established. The proprioception measures (JPS-DE, JPS-AE, and JPS-VE) for differentiating the ankle perception deficits were demonstrated. Abstract: Background and objective: Ankle motion and proprioception in multiple axis movements are crucial for daily activities. However, few studies have developed and used a multiple axis system for measuring ankle motion and proprioception. This study was designed to validate a novel ankle haptic interface system that measures the ankle range of motion (ROM) and joint position sense in multiple plane movements, investigating the proprioception deficits during joint position sense tasks for patients with ankle instability. Methods: Eleven healthy adults (mean ± standard deviation; age, 24.7 ± 1.9 years) and thirteen patients with ankle instability were recruited in this study. All subjects were asked to perform tests to evaluate the validity of the ankle ROM measurements and underwent tests for validating the joint position sense measurements conducted during multiple axis movements of the ankle joint. Pearson correlation was used for validating the angular position measurements obtained using the developed system; the independent t test was used to investigate the differences in joint position sense task performance for people with or without ankle instability. Results: The ROM measurements of the device were linearly correlated with the criterion standards (r = 0.99). The ankle instability and healthy groups were significantly different in direction, absolute, and variable errors of plantar flexion, dorsiflexion, inversion, and eversion (p < 0.05). Conclusions: The results demonstrate that the novel ankle joint motion and position sense measurement system is valid and can be used for measuring the ankle ROM and joint position sense in multiple planes and indicate proprioception deficits for people with ankle instability.